Transformasi Budidaya Cabai Berkelanjutan Melalui Aplikasi Biostimulan di Desa Tanjung Pering: Sustainable Chili Cultivation Transformation Through the Application of Biocompost in Tanjung Pering Village - Fadli, Rahmad; Suwandi (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2026)
The output of chili in Tanjung Pering Village remains low due to diminished soil fertility resulting from the extensive application of synthetic chemicals in cultivation. The elevated incidence of pests and diseases contributes to the inadequate and suboptimal growth and development of plants. The objective of the service activity is to implement sustainable and eco-friendly growing techniques utilizing biological agents. The biological agents utilized include the fungus Trichoderma sp., Beauveria sp., and various other helpful suppressive microbiomes. Biocompost application with biological agents is executed by pouring and directly irrigating the plant's root zone. Post-application observations are systematically performed 24 hours after application, followed by intervals of 14 days. Technical discussions were conducted to enhance farmers' comprehension of the application procedures employed. The application findings indicate enhanced plant growth, characterized by denser foliage, vibrant dark green leaves, an increased quantity of flowers and fruit pistils, and a reduced incidence of insect and disease infestations. The farmers' enthusiasm for participation in each level of the program was clearly visible. The utilization of eco-friendly technology indicates compatibility with the agroecosystem characteristics of the land. In summary, the cultivation technology of chili plants with biological agents has the capacity to enhance productivity and can be sustainably used by farmers